Alternative (κ1-N:η6-arene vs. κ2-N, N) coordination of a sterically demanding amidinate ligand: are size and electronic structure of the Ln ion decisive factors?. Issue 23 (21st May 2019) - Tolpygin, Aleksei O.; Shavyrin, Andrei S.; Cherkasov, Anton V.; Fukin, Georgy K.; del Rosal, Iker; Maron, Laurent; Trifonov, Alexander A.
Abstract : Both ion size and electronic structure of Ln(ii /iii ) ion are decisive in the implementation of either κ 1 -amido : η 6 -arene or κ 2 -N, N′ type of coordination of sterically demanding amidinate ligands. Abstract : The amine elimination reaction of equimolar amounts of ansa -bis(amidine) C6 H4 -1, 2-{NC( t Bu)NH(2, 6-iPr2 C6 H3 )}2 (L 1 H ) and [(Me3 Si)2 N]2 Yb(THF)2 affords a bis(amidinate) Yb II complex [C6 H4 -1, 2-{NC( t Bu)N(2, 6-iPr2 C6 H3 )}2 ]Yb(THF) (1 ) in 68% yield. Complex1 features a rather rare η 1 -amido:η 6 -arene coordination of both amidinate fragments to the Yb II ion, resulting in the formation of a bent bis(arene) structure. Oxidation of1 by I2 regardless of the molar ratio of reagents (2 : 1 or 1 : 1) leads to the formation of the Yb III species [{(2, 6-iPr2 C6 H3 )NC( t Bu)NH}-C6 H4 -1, 2-{NC( t Bu)N(2, 6-iPr2 C6 H3 )}]YbI2 (THF)2 (2 ) in which only one amidinate fragment is coordinated to the ytterbium ion in κ 2 -N, N′-chelating coordination mode, while the second NCN fragment is protonated in the course of the reaction and is not bound to the metal ion. The outcome of the salt metathesis reaction of LaCl3 with lithium amidinates [C6 H4 -1, 2-{NC( t Bu)N(2, 6-R2 C6 H3 )}2 Li2 ] (R = Me, iPr) is proven to be strongly affected by the substituent 2, 6-R2 C6 H3 on the amidinate nitrogens. When R = iPr, the salt metathesis reaction occurs smoothly and results in the formation of an ate -chloro-amidinate complex [C6 H4 -1, 2-{NC( t Bu)N(2, 6-iPr2 C6 H3 )}2 ]La(μ 2 -Cl)Li(THF)(μ 2 -Cl)2 Li(THF)2 (3 ) in which the La III ion is coordinated by both amidinate fragments in a "classic" κ 2 -N, N′-chelating fashion. In the case of R = Me, the reaction requires prolonged heating for completion. Moreover, the salt metathesis reaction is accompanied by the fragmentation of the ligand and affords a trinuclear chloro-amidinate complex [C6 H4 -1, 2-{NC( t Bu)N(2, 6-Me2 C6 H3 )}2 ]La{[( t Bu)C(N-2, 6-Me2 C6 H3 )2 ]La(THF)}2 (μ 2 -Cl)4 (μ 3 -Cl)2 (4 ) containing one dianionic ansa -bis(amidinate) and two monoanionic [( t Bu)C(N-2, 6-Me2 C6 H3 )2 ] amidinate fragments. DFT calculations are conducted to determine the factor that governs this change in coordination mode and, in particular, the effect of the metal oxidation state.